A Synopsis of Orthotrichum s. lato (Bryophyta, Orthotrichaceae) in China, with Distribution Maps and a Key to Determination - Plášek, Vítězslav; Komínková, Zuzana; Ochyra, Ryszard; Fialová, Lucie; Guo, Shuiliang; Sulayman, Mamtimin (Plants (Basel, Switzerland), 2021)
A total of 46 species and two varieties of the traditionally interpreted genus Orthotrichum are currently known to occur in China. They represent five genera, including Orthotrichum (29 species), Lewinskya (14 species and two varieties), and Nyholmiella and Leratia that are represented by a single species each. The fifth genus Florschuetziella, also consisting of only one species, F. scaberrima, is an entirely neglected representative of the China's moss flora. A list of all accepted taxa is presented and for each taxon all literature records and herbarium specimens are enumerated for provinces in which they have been recorded, and their distribution is mapped. A key to determination of Chinese orthotrichalean mosses is presented. A chronological list of 63 species and varieties and two designations, O. catagonioides and O. microsporum which have never been validly published, reported from China in the years 1892-2020 is presented. Four species, Orthotrichum brasii, O. hooglandii, O. elegans and O. gymnostomum are excluded from the bryoflora of China and Lewinskya affinis var. bohemica and Orthotrichum schimperi are recorded for the first time from this country. Phytogeography of the Chinese taxa of the orthotrichalean mosses is considered and they are grouped into eight phytogeographical elements and five sub-elements.
Keywords: Musci; distribution; Orthotrichaceae; Asia; floristic elements; phytogeography; endemics; bryophytes